Холодная гибка стальных прямоугольных труб в трубогибе с проточкой специального профиля на фасонном валке - Калюжный, Владимир Леонидович; Олександренко, Ярослав Сергеевич; Куликов, Иван Петрович (НТУ "ХПИ", 2016)
С использованием метода конечных элементов изучен известный способ холодной гибки на определенный радиус стальных прямоугольных труб в трубогибе с проточкой специального профиля на фасонном валке, на которой посередине расположен выступ. Для сравнения результатов было проведено моделирование формообразования для трех значений величины диаметра указанного выступа. Деформированию подвергались прямоугольные трубы из стали 10. Определены зависимости момента гибки стальных прямоугольных труб от угла поворота фасонного валка. Установлены конечные формы и размеры полученных холодной гибкой изделий, а также определено напряженно-деформированное состояние и степень использования ресурса пластичности сдеформированного металла. Наблюдается отсутствие гофр, складок на изделиях и контакта боковой поверхности изделия с стенками фасонного валка, что гарантирует простоту извлечения изделия из рабочей зоны трубогиба. Установлено увеличение эффективности процесса гибки стальных прямоугольных труб в трубогибе с уменьшением величины диаметра выступа на рабочей поверхности фасонного валка.

Interest in large-scale industrial enterprises to technology bending of steel rectangular pipes is steadily increasing. The greatest distribution they received in the shipbuilding, power engineering, automotive and aircraft industry – for the manufacture of the frame elements of various steel structures, ships, airplanes, cars. Using the finite element method investigated the known method of cold bending for a certain range of steel rectangular pipes on pipe bender with special profile groove on the shaped roller, the ledge is located in the middle of special profile groove. For comparison of the results, simulation of forming was conducted for three values of ledge’s diameter. Subjected to deformation the rectangular pipes of steel 10. There’re identified dependence of the rectangular steel pipe bending’s moment of the angle of rotation of the shaped roller. Identified the final shape and size of the products obtained by cold bending, as well as stress-strain state and the degree of using of the resource of plasticity in deformed metall. There is a lack of corrugations, folds on the products and contact the side surface of the product with walls shaped roller, which ensures ease removal of product from the working zone of the pipe bender. Established increase efficiency of the process of cold bending of steel rectangular pipes on pipe bender with decreasing of value of ledge’s diameter on the working surface of the shaped roller.
Cold bending of steel rectangular pipes on pipe bender with special profile groove on the shaped roller
Keywords: холодная гибка; трубогиб; фасонный валок; специальный профиль; проточка; прямоугольная труба; метод конечных элементов; момент гибки; конечная форма; конечные размеры; напряженно-деформированное состояние; cold bending; pipe bender; shaped roller; special profile groove; rectangular pipe; finite element method; bending’s moment; final shape; final size; stress-strain state